Os fazeres com as linguagens artísticas à luz da abordagem de Reggio Emilia: a experiência da própria prática - Rala, Cássia Antunes Almeida Batalin (Universidade Federal de São Carlos, 2020)
The present work was born out of concerns about educational practices in Early Childhood Education at a school in the city of Sorocaba/SP/Brazil inspired by the Reggio Emilia approach. From the routine of the classroom, the need to analyze the approximations and distances between this approach and the reality of the Sorocaban classroom emerged. The research, of bibliographic nature with analysis of field data about the own practice, sought to know the Italian approach and the way in which it comprehends early childhood education, the importance of the studio and artistic languages in the schools of Reggio Emilia and unveiling similarities and contrasts regarding the observed reality. Since copying a model and applying it without contextualization implies disregarding people´s history and culture, as well as disregarding the community to which they belong, the research sought to contribute with reflections on ways to consider the needs of the local reality to build an excellent education quality for all children. It was found that art making according to Reggio Emilia's approach involves understanding the child as a protagonist, powerful and possessing his/her own languages and manners, in addition to requesting the presence of an educator capable of mediating and creating situations of exploration, creation and learning construction.
Making with artistic languages according to Reggio Emilia's approach: the experience of own practice
Keywords: Educação Infantil; Early Childhood Education; Ensino de Arte; Art teaching; Reggio Emilia; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO